PATHOGENETIC ASPECTS OF ATHEROTHOMBOTIC RISK IN OBESITY AND THROMBOPHILIA - A. V. Khromylev (IRBIS LLC, 2016)
The assosiation between obesity, cardiovascular diseases and thrombosis is well-known and is caused by proinflammatory and prothombotic status in obesity. Numerous hormones and cytokines, secreted by adipocytes, influence the gene expression and function of endothelial cells, arterial smooth muscle cells, and monocytes leading to the development of an atherosclerotic plaque. Also, variety of cytokines produced by adipocytes controls endothelial function, hemostatic and fibrinolytic systems, platelet function, affecting progression of thombus formation. Nowadays,pathogenetic mechanisms of this relationship are under active study. Thrombophilia is another independent risk factor of tromboembolic complications.